Evaluating the Anti-Osteoporotic Potential of Mediterranean Medicinal Plants: A Review of Current Evidence - Alhareth Abdulraheem Al-Ajalein; Nurul 'Izzah Ibrahim; Mh Busra Fauzi; Sabarul Afian Mokhtar; Isa Naina Mohamed; Ahmad Nazrun Shuid; Norazlina Mohamed (MDPI AG, 2024)
Background: Bones are biological reservoirs for minerals and cells, offering protection to the other organs and contributing to the structural form of the body. Osteoporosis is a prevalent bone condition that significantly impacts people's quality of life. Treatments utilizing natural products and medicinal plants have gained important attention in the management of osteoporosis and its associated implications, such as osteoporotic fractures. Even though thousands of plants grow in the Mediterranean region, the use of medicinal plants as an alternative therapy for osteoporosis is still limited. Methods: This article provides a comprehensive overview of seven Mediterranean medicinal plants that are used in osteoporosis and osteoporotic fractures in in vitro, in vivo, and clinical trials. The mechanism of action of the medicinal plants and their bioactive compounds against diseases are also briefly discussed. Results: The findings clearly indicate the ability of the seven medicinal plants (Ammi majus, Brassica oleracea, Ceratonia siliqua L., Foeniculum vulgare, Glycyrrhiza glabra, Salvia officinalis, and Silybum marianum) as anti-osteoporosis agents. Xanthotoxin, polyphenols, liquiritin, formononetin, silymarin, and silibinin/silybin were the main bioactive compounds that contributed to the action against osteoporosis and osteoporotic fractures. Conclusions: In this review, the Mediterranean medicinal plants prove their ability as an alternative agent for osteoporosis and osteoporotic fractures instead of conventional synthetic therapies. Thus, this can encourage researchers to delve deeper into this field and develop medicinal-plant-based drugs.